A data-driven selection of the number of clusters in the Dirichlet allocation model via Bayesian mixture modelling. Issue 15 (13th October 2019) - Saraiva, E. F.; Pereira, C. A. B.; Suzuki, A. K.
ABSTRACT: In this paper, we consider a Bayesian mixture model that allows us to integrate out the weights of the mixture in order to obtain a procedure in which the number of clusters is an unknown quantity. To determine clusters and estimate parameters of interest, we develop an MCMC algorithm denominated by sequential data-driven allocation sampler. In this algorithm, a single observation has a non-null probability to create a new cluster and a set of observations may create a new cluster through the split-merge movements. The split-merge movements are developed using a sequential allocation procedure based in allocation probabilities that are calculated according to the Kullback–Leibler divergence between the posterior distribution using the observations previously allocated and the posterior distribution including a 'new' observation. We verified the performance of the proposed algorithm on the simulated data and then we illustrate its use on three publicly available real data sets.